Effectiveness of Micro, Small and Medium Enterprises (MSME) Program to Increasing Civic Economy Creativity Towards Socio-Economic Problem Women's Welfare - Rivi Ahmad Jalari; Endang Danial; Prayoga Bestari (Jurnal Civicus, 2023)
As one aspect of being a citizen who is motivated by economic problems that take place in an area of Bandung Regency which is famous for its superior products run by socio-economic vulnerable women with assistance from the local government through the Family Welfare Program, this implementation is a factor in meeting needs. Micro, Small and Medium Enterprises (MSME) are one of the implementations of the economy civic that emphasizes an aspect of community benefits, this research is motivated by a qualitative approach with a case study method conducted in Tanjungsari Village, Cangkuang District, Bandung Regency, and the results of the study show that there is a formation of creativity in oneself. them as business actors from the results of observations, interviews, and documentation studies with data analysis in the form of data reduction. This shows that the implementation of Micro, Small and Medium Enterprises (MSME) activities that increase creativity in PRSE is part of the economy civic as well as an increase in the economic impact of the community.